Combined modality therapy for patients with esophageal squamous cell carcinoma: Radiation dose and survival analyses. Issue 2 (9th November 2022) - Shueng, Pei‐Wei; Huang, Chun‐Chieh; Liu, Yu‐Ming; Wu, Yuan‐Hong; Huang, Pin‐I; Yen, Sang‐Hue; Lin, Kuan‐Heng; Hsu, Chen‐Xiong
Abstract: Background: We aimed to analyze the radiation dose and compare survival among combined modality therapy using modern radiation techniques for patients with esophageal squamous cell carcinoma (ESCC). Methods: This retrospective study included patients with clinically staged T1‐4N0‐3M0 ESCC from 2014 to 2018. Patients who received combined modality therapies with curative intent were enrolled. The overall survival (OS) rates among combined modality therapy were compared. The clinical variables and impacts of radiation dose on survival were analyzed by the Kaplan–Meier method and Cox regression model. Results: Of the 259 patients, 141 (54.4%) received definitive concurrent chemoradiotherapy (DCCRT); 67 (25.9%) underwent neoadjuvant chemoradiotherapy followed by surgery (NCRT+S); 51 (19.7%) obtained surgery followed by adjuvant chemoradiotherapy (S+ACRT). Two‐year OS rates of the DCCRT, NCRT+S and S+ACRT group were 48.9, 61.5 and 51.2%. In the subgroup analysis of DCCRT group, the 2‐year OS of patients receiving radiation dose 55–60 Gy was 57.1%. Multivariate analyses showed that clinical stage ( p = 0.004), DCCRT with 55–60 Gy ( p = 0.043) and NCRT+S with pathological complete response (pCR) ( p = 0.014) were significant prognostic factors for better OS. The radiation dose–survival curve demonstrated a highly positive correlation between higher radiation dose and better survival. Conclusion: Our results suggest that NCRT+S can provide a favorable survival for patients with ESCC, especially in patients who achieved pCR. The optimal radiation dose might be 55–60 Gy for patients receiving DCCRT via modern radiation techniques. Further randomized clinical studies are required to confirm the survival benefits between NCRT+S and DCCRT with escalated dose. Abstract : (a) Overall survival (Kaplan–Meier method) stratified by combined therapy. DCCRT with radiation dose 55–60 Gy may have a potential comparable 2‐year overall survival as compared with NCRT+S group (57.1% vs. 61.5%). (b) Radiation dose–survival curve of the patients receiving DCCRT. Patients are divided into the 45–50 Gy, 50–55 Gy, 55–60 Gy and 60–65 Gy groups. There is a highly positive correlation ( R 2 = 0.997) between the higher radiation dose and better survival.